Who assimilates? Statistical artefacts and intergenerational mobility in immigrant families - Renee Reichl Luthra; Thomas Soehl (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper assesses estimates of immigrant intergenerationa l mobility that are based on aggregate data sources. We show that aggregation bias strongly inflates estimates of the relationship between immigrants' educational attainment and the educational attainment of their children. Compared to natives, the educational transmission process between parent and child is much weaker in immigrant families. A number of group-level processes, such as societal discrimination, ethnic segregation, or ethnic networks, may render group characteristics more important predictors of second generation educational attainment than parental education.
Keywords: I21; J15; J62; 330; immigration; intergenerational mobility; education